(untitled) (Journal of the College of Basic Education, 2026)
Qur’anic discourse occupies a vast and profound domain within linguistic, rhetorical, and literary studies, owing to its expressive and stylistic beauty that surpasses all other poetic or literary forms. Allah, Glorified and Exalted be He, has distinguished His revealed Book to the Prophet Muhammad (peace and blessings be upon him and his family) with a miraculous nature rooted in language itself. It is well established that the Holy Qur’an is inimitable—no one, whether from the ancients or the moderns, has ever been able to produce anything comparable to it. Its essence and the pinnacle of its miraculousness lie in its linguistic and rhetorical structure. As Dr. Fadhil Al-Samarrai observes: "The miraculousness of the Qur’an is multifaceted and multidimensional, and it is impossible for a single scholar—or even a group of scholars in any given era, regardless of the breadth of their knowledge and diversity of their expertise—to fully encompass it. They can only uncover certain aspects of its secrets across various domains.” From this standpoint, the present study examines selected Qur’anic verses that refer to the Prophet’s Household (peace be upon them), including Imam al-Husayn (peace be upon him). The study seeks to uncover the aesthetic dimensions of Qur’anic eloquence, focusing on the rhetorical artistry and stylistic devices that contribute to its unique expressive beauty.